Experiences in Teaching Finance in English - Jorge Octavio Restrepo Guzman (Universidad de La Sabana, 2010)
This paper presents a brief description of English Content Based Instruction (CBI) as a process in which the student gains mastery of the language (procedural knowledge) and mastery of the subject learned (declarative knowledge) and the characteristics of its integration in the teaching process. Also, the author describes his experiences in planning and giving a course on Financial Analysis using the techniques of CBI and student-centered learning and the tools and procedures used in performing this task. Furthermore the experiences of other universities in giving CBI courses are reflected upon. The result of a survey about the perception of the course among a representative sample of the students is presented and analyzed and suggests.